Crossed swords : Pakistan, its army, and the wars within - Nawaz, Shuja (Karachi; Oxford University Press, 2008)
"Based on 30 years of research and analysis, this definitive book is a profound, multi-layered, and historical analysis of the nature and role of the Pakistan Army in the country's polity as well as its turbulent relationship with the United States."--Jacket
Includes Bibliographical &index
Keywords: Pakistan Politics and government; Politics and government; Pakistan. Army Political activity